PRODUKSI BERSIH PADA AKTIVITAS DOMESTIK DAN PUBLIK WANITA NELAYAN DI SELANGAN LAUT KOTA BONTANG - Elly Purnamasari (2339-1324, 2014)
The major aim of this research was to determine the application of net production as management strategy for fisher women activity in Selangan Laut of Bontang City in the field of integrated domestic and public sectors in order to increase the quality life of fishers family. The results showed that fisher women activities were classified as follows: (a) in domestic sector such as performing meals for the family; (b) in social aspect like providing meals for public/specific events, and (c) in productive one, i.e. the making of fish paste, sea weeds processed product, and salted and dried fishes, the performance of grilled fish culinary services and sea weeds cultivation activity. The activities above have a prospect to implement the net production. The application of net production can be done by managing and utilizing solid and liquid wastes. In addition, the further efforts to ensure net production are formulating procedure operation standard of net production, organizing raw materials and their supplement by the creation of ‘come in first come out first’ model, preparing adequate equipments, increasing the number of demand, and extending market channel through the creation of product diversification, modification and packaging